2020
DOI: 10.3389/fneur.2020.00866
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of T-SPOT.TB Assay for Tuberculous Meningitis: An Updated Meta-Analysis

Abstract: Background: The role of T-SPOT.TB (T-SPOT) assay for tuberculous meningitis (TBM) diagnosis has not been fully assessed. Here, we conducted an updated meta-analysis to evaluate the diagnostic accuracy of peripheral blood (PB) T-SPOT and cerebrospinal fluid (CSF) T-SPOT for diagnosing TBM. Methods: Relevant studies in the PubMed database, EmBase database, Cochrane database, Scopus database, Google Scholar, China National Knowledge Internet, and Wan-Fang database were retrieved from August 1, 2005, to June 22, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Nevertheless, a recent meta-analysis conducted by Luo et al. ( 13 ) revealed a pooled sensitivity of 78% and specificity of 68% using peripheral blood T-SPOT and a pooled sensitivity of 76% and specificity of 88% using CSF T-SPOT in the diagnosis of TBM. Beyond that, indeterminate results are commonly noted, as sufficient sample volumes are usually unavailable, further limiting the use of CSF T-SPOT in clinical practice ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a recent meta-analysis conducted by Luo et al. ( 13 ) revealed a pooled sensitivity of 78% and specificity of 68% using peripheral blood T-SPOT and a pooled sensitivity of 76% and specificity of 88% using CSF T-SPOT in the diagnosis of TBM. Beyond that, indeterminate results are commonly noted, as sufficient sample volumes are usually unavailable, further limiting the use of CSF T-SPOT in clinical practice ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, Luo et al included 27 articles and showed that, for TBM diagnosis, the pooled sensitivity and specificity of blood T-SPOT.TB were 0.78 and 0.68, and the pooled sensitivity and specificity of CSF T-SPOT.TB were 0.76 and 0.88 [ 50 ]. However, this research also included intracranial tuberculoma patient data for one article [ 20 ] and overlapping datasets in four articles [ 21 , 36 , 48 , 49 ], causing unreliable pooled results.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Escherichia coli, Mycobacterium kansasii, or Mycobacterium gordonae infection can cause false positives in experimental results (145). A recent study found that large volumes are required to get adequate cerebrospinal fluid mononuclear cells when the assay is used on cerebrospinal fluid, which hinders its clinical use (146). Therefore, the specificity and sensitivity of T-SPOT ® needs to be further improved.…”
Section: Potential Of Mscs To Diagnosementioning
confidence: 99%